Simple and efficient anionic polymerization of N‐phenylmaleimide with fluorides as an initiator. Issue 30 (31st December 2019) - Wu, Jingbo; Sun, Shasha; Novak, Bruce M.
ABSTRACT: The facile anionic polymerization of N ‐phenylmaleimide ( N ‐PMI) using fluorides as an initiator has been discovered and systematically investigated. Effect of different solvents such as dioxane, tetrahydrofuran, dichloromethane (DCM), dimethyl sulfoxide (DMSO), N ‐methylpyrrolidone, acetonitrile, toluene, and acetone and effect of anionic initiators such as tetra‐ n ‐butylammonium fluoride (TBAF), cesium fluoride, and potassium fluoride have been studied. The kinetics of polymerization using TBAF as an initiator in DMSO is also studied. Some of the resulting poly(PMI)s are characterized by gel permeation chromatography, solubility test, attenuated total reflection‐Fourier transform infrared, nuclear magnetic resonance (NMR), and 13 C‐NMR spectral analysis. The thermal behaviors are studied by thermogravimetric and differential scanning calorimetric analysis. A proposed polymerization mechanism is also discussed. Our results show fluoride can effectively induce the polymerization of N ‐PMI in various solvents under very mild conditions with good to excellent yields. © 2019 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2019, 137, 48909. Abstract :